Neoliberal ideologization of work and the beginning of unionisation in the video game industry - Maravić, Manojlo (Sociološki pregled, 2023)
The paper addresses the current issue of crunch, which is one of the most common reasons for high employee turnover in the video game industry. This paper aims to identify the ideological assumptions that underlie this industry, their manifestation in work practices, the consequences, and possibilities for resistance. The ideologization of labour implies the process of creating implicit knowledge, values, beliefs, and hegemonic discourses of neoliberalism that normalise and enable the policy of management. In this, the shaping of emotions of passion and love for work plays an important role, which functions through the hybridisation of working hours and leisure, work and home space, company, and family. To form a union awareness in the video game industry, it is necessary to first understand this ideological structure.